1998
DOI: 10.1097/00000542-199801000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Cardiac Sodium Current by Inhalational Anesthetics in the Absence and Presence of β-Stimulation 

Abstract: These results suggest two distinct pathways for volatile anesthetic modulation on the cardiac Na+ current: (1) involvement of G proteins and a cyclic adenosine monophosphate (cAMP)-mediated pathway for halothane and, (2) a G-protein-dependent but cAMP-independent pathway for isoflurane. Furthermore, these studies show that the inhibition of cardiac INa by isoproterenol is enhanced in the presence of halothane, suggesting some form of synergistic interaction between halothane and isoproterenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
3
17
0
1
Order By: Relevance
“…Furthermore, inactivation of the inhibitory G iα protein as demonstrated previously (Böhm et al, 1994) appears to be involved in the facilitation of halothane-, but not isoflurane-associated cardiac dysrhythmias (Weigt et al, 1998b). Similarly, I Na was reduced upon β-adrenergic stimulation by isoproterenol (1 μmol/L), and this inhibition was potentiated by halothane and somewhat less by isoflurane (Weigt et al, 1998a). In case of halothane, this synergistic effect was reduced in the presence of the G protein inhibitor GDPβS and a specific PKA inhibitor, whereas PKA inhibition had no effect in case of isoflurane (Weigt et al, 1998a).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Furthermore, inactivation of the inhibitory G iα protein as demonstrated previously (Böhm et al, 1994) appears to be involved in the facilitation of halothane-, but not isoflurane-associated cardiac dysrhythmias (Weigt et al, 1998b). Similarly, I Na was reduced upon β-adrenergic stimulation by isoproterenol (1 μmol/L), and this inhibition was potentiated by halothane and somewhat less by isoflurane (Weigt et al, 1998a). In case of halothane, this synergistic effect was reduced in the presence of the G protein inhibitor GDPβS and a specific PKA inhibitor, whereas PKA inhibition had no effect in case of isoflurane (Weigt et al, 1998a).…”
supporting
confidence: 60%
“…Interestingly, coexpression experiments of Na + channel α-subunits from skeletal muscle, brain, and cardiac muscle with PKC in Xenopus oocytes have shown that halothane (1 mmol/L) was without effect on any of the three isoforms when expressed alone, but reduced Na + current after PKC coexpression, with skeletal and neuronal isoforms being markedly more sensitive than the cardiac one (Patel et al, 2000). Potential synergistic effects of volatile anesthetics with PKC and PKA pathways on cardiac Na + current have been investigated in guinea pig ventricular myocytes using the α 1 -and β-adrenoceptor agonists methoxamine and isoproterenol, respectively, and other tools interfering with G proteins and kinases (Weigt et al, 1997b(Weigt et al, , 1998a(Weigt et al, , 1998b. Methoxamine decreased I Na in a concentration-and voltage-dependent manner, being more potent at depolarized potentials, and halothane (1.2 mmol/L) and isoflurane (1.0 mmol/L) interacted synergistically with methoxamine to reduce I Na around the physiologic cardiac resting potential (Weigt et al, 1997b).…”
Section: Cardiac Sodium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been discussed for L-type Ca 2þ channels, it is important to consider interference of anesthetics with regulatory pathways. Halothane evoked an attenuation of Na þ currents by complex interactions with pathways involving G proteins and cAMP (115). For isoflurane, pharmacological evidence has been presented showing that it interacted with G proteins (partly distinct from those affected by halothane) and with protein kinase C (116).…”
Section: Na + Channelsmentioning
confidence: 99%
“…Pathophysiological implications have been described: PKC modulation is at least partially responsible for the modulatory action of lysophosphatidylcholine, which has been implicated in arrhythmogenesis during ischemia [134][135][136]. Furthermore, cardiac dysrhythmias during inhalation anesthesia by halothane and isoflurane are also related to PKA-and PKC-mediated phosphorylation of cardiac sodium channels [137,138]. …”
Section: Cardiac Sodium Channelmentioning
confidence: 99%